2018
DOI: 10.1089/jwh.2016.6140
|View full text |Cite
|
Sign up to set email alerts
|

Young Women's Perceptions Regarding Communication with Healthcare Providers About Breast Cancer, Risk, and Prevention

Abstract: Background Women younger than 45 years old have lower rates of breast cancer, but higher risk of recurrence and mortality after a cancer diagnosis. African American women are at risk for early onset and increased mortality; Ashkenazi Jewish women are at risk for genetic mutations leading to breast and ovarian cancer. Although younger women are encouraged to talk to doctors about their family history, little is known about these discussions. Materials and Methods In 2015, 167 women aged 18–44 years participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Several factors, either individually or in combination, likely contribute to the lower cancer screening knowledge among minorities observed here. Factors identified in previous work include overall lower education attainment as well as missed opportunities for counseling and recommendation by providers 38 , 39 . One of the most likely contributors to lower screening knowledge is decreased health literacy among minority populations, which is an underlying issue for low uptake of many health-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, either individually or in combination, likely contribute to the lower cancer screening knowledge among minorities observed here. Factors identified in previous work include overall lower education attainment as well as missed opportunities for counseling and recommendation by providers 38 , 39 . One of the most likely contributors to lower screening knowledge is decreased health literacy among minority populations, which is an underlying issue for low uptake of many health-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 24.8% of women referred to the Spoke centers by GPs were younger than 35 years, such as women sent by specialists were mostly inclusive between 40 and 44 years (23.4%). As already seen in a recent paper that investigated the young women's perceptions regarding communication with healthcare providers about BC risk, people aged 18‐29 years asked more than doctors about their risk, whereas women in the age group between 30 and 44 years were likely queried by GPs about their family history . Totally, only 34% of all women evaluated at the Spoke centers aged less than 45 years and this could represent a critical issue, in order to offer a very preventive strategy in young individuals at hereditary‐HR for BC.…”
Section: Discussionmentioning
confidence: 99%
“…This could possibly be the fact that not all individuals with family cancer history might need more frequent screenings. However, findings also point to the potential missed opportunities for needed screening referrals and the critical need of doctor training for culturally sensitive communication and screening this higher risk group (Lunsford et al, 2018;Rose, et al, 2001).…”
Section: Practical Implicationsmentioning
confidence: 95%
“…Similarly, another large colorectal cancer study in Iran examined first degree relatives (FDRs) of cancer patients also showed low screening rate and knowledge, and low awareness of their own increased cancer risk (Salimzadeh et al, 2016). These unsatisfactory findings may at least partially due to the fact that general physicians need to be educated to better perform their gatekeeper role and answer screening related questions among patients with family cancer history (Lunsford et al, 2018;Rose et al, 2001). Rose and colleague studied physician's knowledge on referring patients with family history of cancers showed that primary care doctors have difficulty in deciding whether to refer due to limited genetic knowledge.…”
Section: The Role Of Family Cancer History On Doctor-patient Cancer Screening Communicationmentioning
confidence: 99%